Pengaruh Motivasi Belajar Terhadap Kemampuan Berpikir Kritis Matematis Siswa - Jelita, Arni Asih; Isnaniah, Isnaniah; Yusri, Fadhilla; Imamuddin, M. (Indo-MathEdu Intellectuals Journal, 2024)
The aim of this research is to determine the significant influence of learning motivation on the mathematical critical thinking abilities of class VII students at MTsN 11 Agam. The hypothesis in this research is "There is a significant influence of learning motivation on the mathematical critical thinking abilities of class VII students at MTsN 11 Agam for the 2023/2024 academic year." This type of research is ex post facto research with a type of correlation research (causal research). The population in this study were all class VII students, totaling 124 students. Meanwhile, the sample in this study was taken randomly as many as 38 students. Before sampling, normality and homogeneity tests were carried out. The instruments used in this research were a mathematics learning motivation questionnaire and mathematical critical thinking ability test questions.  The statistical analysis technique used is Simple Regression Analysis. From the results of data analysis, it shows that the regression equation between motivation to learn mathematics and critical mathematical thinking abilities of class VII students at MTsN 11 Agam is Y=10.396+0.2714X with a correlation of 0.628 and a coefficient of determination of 39.5%. The results of hypothesis testing obtained t_count > t_table, namely 4.843 > 2.028, and the SPSS results obtained a significant 0.00 and the value α=0.05, so it was obtained 0.00 ≤ 0.05. It can be concluded that there is a significant influence of motivation to learn mathematics on the mathematical critical thinking abilities of class VII students at MTsN 11 Agam.